A potential role of hydrogen sulfide (H₂S) in the regulation of the Ras-ERK signaling-dependent transcription of DNA methyltransferases - Nikitina, T.A. (Вiopolymers and Cell, 2016)
Ras-ERK cell signaling regulates transcription of DNA methyltransferases (DNMTs). A role of H₂S in regulation of the Ras-ERK signaling activity and DNMTs expression has also been shown. Here we propose a hypothesis that H₂S regulates the Ras-ERK signaling-dependent DNMTs transcription. Oxidative stress, lipid metabolism, protein sulfhydration, nitrosylation and nitration are the main targets of regulation by H₂S. These cell processes are important for the post-translational modifications (PTMs) of the Ras-ERK signaling pathway enzymes. We provide evidence for the dependence of DNMTs transcription on the PTMs of the enzymes of Ras-ERK signaling pathway regulated by H₂S.